Monte Carlo simulation of anisotropic Shastry-Sutherland lattice in the framework of classical Heisenberg model - Slavin, V.V.; Krivchikov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Monte Carlo simulation of two-dimensional Shastry–Sutherland lattice has been carried out using heat-bath method. The dependencies of magnetization M on external field H have been obtained in the framework of classical Heisenberg model. In certain interval of exchange parameters ratio the plateau of magnetization corresponding to M = 1 / 3 has been observed. The influence of exchange anisotropy of “easy-axis” type on this plateau width is studied. It has been shown that even weak anisotropy ( 1− 2% ) leads to essential enlargement of the plateau. The dependence of critical temperature on exchange parameters ratio has been established.